Tradução entre ciências e proteção de bacias hidrográficas de importância para conservação : Ivaí e Piquiri, remanescentes fluviais do alto rio Paraná. - Azevedo, Robertson Fonseca de (2015)
We analyze, in a qualitative way, the contention efforts (resistance, confrontation) against the development of dams in the Ivaí and Piquiri rivers and their tributaries, keeping track of the activities set forth by the "Pró Ivaí/Piquiri" movement, created with the goal to promote the integration of knowledges and interests associated with the conservation of those river basins. In addition, we quantify and describe the opportunities created to allow the contact between different social actors (lawyers, scientists from different fields, local managers and lay people) which were used to exchange knowledge. The issues that have delineated the approach of this work were: the circumstances led to the institutional mobilizations favoring the protection of the Ivaí and Piquiri basis, in face of projects for the implementation of dams on them. The institutions took part in this process and their ways of action. The strategies used in the resistance to the implementation of dams, and the instruments conceived in order to promote the exchange of knowledge between different Academic fields and the communities threatened by hydropower projects in the region. The education of the communities was important in the contention efforts against activities that would be detrimental to environmental quality of their territory. did this knowledge reach "contention"? We have investigated the regional contention movement resisting the use of the Ivaí and Piquiri basins for electricity production and the role of circulation/transfer/socialization/collaborative production of knowledge in the protection of those basins. In this way, we have: described the history of the articulated resistance against dams (still happening) in the Ivaí and Piquiri basins. Analyzed the process of translation among knowledges, exchange of information and have presented the mechanism used to make those expertizes flow throughout the different actors of the contention effort. Proposed, from this case study, a toolbox potentially replicable in similar situations, which we presume will happen if the policy for energy production in the country does not change.